Entrepreneurship and quality of institutions: A developing-country approach - José Ernesto Amorós (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
Over the last few years we have observed a prominent flourishing of empirical studies on the determinants of new business creation and its effect on the economy. The present study focuses on an important determinant of entrepreneurship: the quality of institutions. This paper is an empirical exploratory work that has the objective of uncovering the relationships between entrepreneurial dynamics and different variables related to the quality of government institutions, with an emphasis on developing countries. The study is based on the panel data of 60 countries that participated in the Global Entrepreneurship Monitor (GEM) project. The results indicate that the quality of institutions is a relevant factor for the distribution and type of entrepreneurial activities. Some implications for public policy are discussed.
Keywords: L26; H11; L53; O57; 330; entrepreneurship; government institutions; Global Entrepreneurship Monitor